Corporate Social Responsibility PT. Pembangunan Jaya Ancol, Tbk Case Study: Ancol Sayang Lingkungan - Herpatria, Rajasa; Rudito, Bambang (Journal of Business and Management, 2013)
DKI Jakarta as the capital city of Indonesia has a myriad of problems, one of which is low environmental hygiene, and high unemployment rates. The improvement of low environmental hygiene, and low employment rate should start from every area in DKI Jakarta. In this final project, author wants to evaluate the program of Ancol Sayang Lingkungan, who was the Corporate Social Responsibility program from PT. Pembangunan Jaya Ancol, Tbk. Purposed to improve environment hygiene, and increase work field in Ancol, which will be the answer of the problem stated above. The Purpose of this final project is to achieve evaluations for community development program of PT. Pembangunan Jaya Ancol, Tbkwhich is AncolSayangLingkungan. This project purpose is to analyze the effectiveness of the program. The results of the program will also be analyzed to discover whether it is already accomplish its target or not. The Author will analyze the relation between every parties involved in implementing the program to determining the successes of social development, and hygiene in the society and also environment. To achieved the objective above the Author using, some theory such as Theory Independent Literally, Community Development, Corporate Social Responsibility Theory, and Theory of CSR Programs effectiveness to society or environmental. And to get the result the Author using these methodology Research Design, Problem Identification, Data gathering, Data Analysis and Conclusion. And conclusion of this is research is AncolSayangLingkungan has give big contribution by increasing hygiene in Ancol, it shown from the questionnaire result that shows increasing number of people awareness towards environmental hygiene. AncolSayangLingkungan also succed in decreasing unemployment rate in Ancol, it is shown by the questionnaire result that stated increasing amount of employment in Ancol. For the recommendation, First, do some improvement in AncolSayangLingkungan sub-programs, PT. Pembangunan Jaya Ancol, Tbk should create new sub-program that attract younger people in Ancol. Second, PT. Pembangunan Jaya Ancol, Tbk should make database of the participant’s, including the participant’s activity progress, as supporting device to easily controlling the participant’s progress. keywords: corporate social resposibility, ancolsayanglingkungan, case study.---------------------------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.